Effects of Different Half-Time Re-Warm Up on Vertical Jump During Simulated Basketball Game (Baltic Journal of Sport and Health Sciences, 2018)
Background. This study investigated the acute eﬀects of diﬀerent half–time re–warm ups on vertical jump height during simulated basketball games. Methods. Ten college level males (age (mean ± standard deviation (SD)), 22.0 ± 5.0 years; weight, 86.0 ± 5.5 kg; height, 193 ± 1 cm.) were divided into two teams, who played three simulated basketball games with three diﬀerent type half-time re-warm ups: aerobic; aerobic + post-activation potentiation exercises and aerobic + post-activation potentiation + stabilization exercises. Counter-movement jump was measured before and during the simulated basketball game at seven time points: before and after warm up, after the 1st, the 2nd quarters, after re-warm up and after the 3rd and the 4th quarters. Simulated basketball games were separated at least by 72 hours. Results. The non-signifcant decrease in Counter-movement jump height during simulated basketball games was observed after executing all three diﬀerent types of half-time re-warm ups. However, Counter-movement jump signifcantly (p < .05) decreased during simulated basketball game only in aerobic type half-time re-warm up game. Conclusion. During simulated basketball game, the least decrease in Counter-movement jump height was observed after aerobic type re-warm up with post-activation potentiation exercises performed at half-time.Keywords: basketball, half-time re-warm up, power, post activation potentiation.